2018
DOI: 10.1016/j.ajpath.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotropic Parasite Toxoplasma gondii Induces Sustained Neuroinflammation with Microvascular Dysfunction in Infected Mice

Abstract: Toxoplasmosis is one of the leading parasitic diseases worldwide. Some data suggest that chronic acquired toxoplasmosis could be linked to behavioral alterations in humans. The parasite infects neurons, forming immunologically silent cysts. Cerebral microcirculation homeostasis is determinant to brain functions, and pathologic states can alter capillarity or blood perfusion, leading to neurodegeneration and cognitive deficits. Albino mice were infected with Toxoplasma gondii (ME49 strain) and analyzed after 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 76 publications
(79 reference statements)
2
43
0
4
Order By: Relevance
“…Pro-inflammatory cytokines induced by T. gondii infection tend to exacerbate the disease itself or symptoms associated with the disease [ 25 , 48 , 49 ]. After infection with T. gondii ME49, pro-inflammatory cytokines appear most frequently in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines induced by T. gondii infection tend to exacerbate the disease itself or symptoms associated with the disease [ 25 , 48 , 49 ]. After infection with T. gondii ME49, pro-inflammatory cytokines appear most frequently in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent animal model study by Estato et al (25), showed that mice infected with T. gondii illustrated an exaggeration of leukocyte adhesion to the endothelial cells that caused endothelial dysfunction. Also, therapy with sulfadiazine improves endothelial dysfunction in acute toxoplasmosis through reduction of parasitic load and related endothelial inflammations (25).…”
Section: Discussionmentioning
confidence: 99%
“…anti-inflammatory cytokines and neurotrophic factors with potential neuroprotective properties, but excessively activated microglia could lead to neuronal apoptosis (Mahmoudvand et al, 2016;Estato et al, 2018).…”
Section: Discussionmentioning
confidence: 99%